The Role of the Civil Service Police Unit (Satpol PP) in Regulating Outdoor Advertising in Semarang City - Wiredarme; Divia Nourma Kusuma Candra (Yayasan Hisnul Muslim Lombok, 2025)
The regulation of outdoor advertising is an important aspect of urban governance, particularly in maintaining spatial order, public safety, and aesthetic quality in rapidly developing cities. In Semarang City, the proliferation of billboards has posed significant regulatory challenges, necessitating effective enforcement by local authorities. This study aims to analyze the role of the Civil Service Police Unit (Satuan Polisi Pamong Praja/Satpol PP) in enforcing outdoor advertising regulations and to identify the factors influencing enforcement effectiveness. This research adopts a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews with key informants from Satpol PP and related local government agencies, complemented by document analysis of regional regulations and official policy documents. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing to ensure analytical rigor and thematic coherence. The findings reveal that Satpol PP has carried out its enforcement mandate through preventive, persuasive, and repressive measures, including regulatory socialization, issuance of warnings, and dismantling of illegal billboards. However, enforcement effectiveness remains suboptimal due to limited institutional capacity, weak inter-agency coordination, and inconsistent implementation practices. Compliance among billboard owners is largely driven by enforcement pressure rather than internalized legal awareness, indicating a weak legal culture in the domain of outdoor advertising regulation. The study also identifies a structural tension between revenue generation objectives and the enforcement of spatial order, which affects regulatory consistency and legitimacy. These findings suggest that enforcement alone is insufficient to achieve sustainable compliance without parallel efforts to strengthen institutional capacity, coordination mechanisms, and public legal awareness. In conclusion, while Satpol PP plays a pivotal role in regulating outdoor advertising in Semarang City, its effectiveness is constrained by structural, procedural, and cultural factors. Strengthening institutional capacity, enhancing inter-agency coordination, and fostering a stronger legal culture are essential to improving enforcement outcomes and advancing sustainable urban governance.